PERAN PEREMPUAN INDONESIA DALAM PERJUANGAN KEBANGSAAN (MEMBACA TOKOH NYAI ONTOSOROH PADA NOVEL BUMI MANUSIA - Adji, Muhamad (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Women have often overlooked in the history of struggle of the Indonesian nation. In the history books of the nation, we are more familiar with men heroic figures than women, so not many know how much women’s roles in the establishment of a nation called Indonesia. Nyai Ontosoroh is a character in the novel Bumi Manusia, by Pramoedya Ananta Toer, who is recognized as the Indonesian literary canon. It is the representation of women who were born and live in the nation before of independence of Indonesian nation. Although born from the lowest class in the structure of Indonesian society and never earned the right to attend school, Nyai Ontosoroh have a large role in the Indonesian struggle until the establishment of an independent Indonesian nation. The questions that guide the writing are 1) how big Nyai Ontosoroh role in the struggle of the Indonesian nation and 2) what role do Nyai Ontosoroh in the struggle of the Indonesian nation. Conclusions obtained from studies that Nyai Ontosoroh is a representation of women in Indonesia who has a big role in realizing national independence of Indonesia. That role not only in the form of concrete action, but the her conviction to have more faith in their own strength than to rely on foreign strenght like the Dutch colonial government